1988
DOI: 10.1038/eye.1988.23
|View full text |Cite
|
Sign up to set email alerts
|

Sorsby's pseudoinflammatory macula dystrophy—Sorsby's fundus dystrophies

Abstract: The findings are presented on the updated Kempster pedigree with Sorsby's fundus dystrophy. The study confirms the features described in other families: autosomal dominant inheritance with complete penetrance, loss of central vision due to subfoveal ingrowth of new vessels, and progressive peripheral chorioretinal atrophy. By contrast to other reports the family in the current study have peripheral retinal dysfunction, a deposit of a subretinal yellow material throughout the fundus and a tritan colour defect, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 7 publications
3
27
0
Order By: Relevance
“…Breaks in Bruch's membrane and other abnormalities of the ECM are also consistently found in other diseases in which CNV occurs. Sorsby's fundus dystrophy is an autosomal dominant inherited disease that shares some phenotypic characteristics with AMD, including extensive ECM deposits along Bruch's membrane, RPE and photoreceptor degeneration, and a high incidence of CNV (Sorsby et al, 1949;Hoskin et al, 1981;Capon et al, 1988;Capon et al, 1989). Affected persons in two pedigrees with Sorsby's fundus dystrophy have a mutation in the tissue inhibitor of metalloproteinase-3 (TIMP-3) gene (Weber et al, 1994), whose product participates in regulation of ECM turnover (Apte et al, 1995).…”
Section: Choroidal Neovascularization the Pathogenesis Of Cnv Is Poormentioning
confidence: 99%
“…Breaks in Bruch's membrane and other abnormalities of the ECM are also consistently found in other diseases in which CNV occurs. Sorsby's fundus dystrophy is an autosomal dominant inherited disease that shares some phenotypic characteristics with AMD, including extensive ECM deposits along Bruch's membrane, RPE and photoreceptor degeneration, and a high incidence of CNV (Sorsby et al, 1949;Hoskin et al, 1981;Capon et al, 1988;Capon et al, 1989). Affected persons in two pedigrees with Sorsby's fundus dystrophy have a mutation in the tissue inhibitor of metalloproteinase-3 (TIMP-3) gene (Weber et al, 1994), whose product participates in regulation of ECM turnover (Apte et al, 1995).…”
Section: Choroidal Neovascularization the Pathogenesis Of Cnv Is Poormentioning
confidence: 99%
“…As a result of studies on Sorsby fundus dystrophy, [68][69][70] it was suggested that a prolonged choroidal filling phase on fluorescein angiography may be a clinical sign of diffuse thickening of Bruch's membrane. In this autosomal dominant condition, a continuous layer of abnormal material of up to 30 mm in thickness is deposited between the inner collagenous layer of Bruch's membrane and the basement membrane of the RPE.…”
Section: Bruch's Membranementioning
confidence: 99%
“…71 In contrast with the normal rapid filling, a contiguous area of prolonged, patchy choroidal fluorescence is seen during the transit phase of fluorescein angiography. [68][69][70] The dye appears initially in the inner choroid as small points of fluorescence that gradually enlarge and coalesce with one another over several frames of the angiogram. Continuous fluorescence indistinguishable from the surrounding normal fundus is not apparent until the late venous phase of the retinal circulation.…”
Section: Bruch's Membranementioning
confidence: 99%
“…Sorsby's fundus dystrophy is an autosomal dominant inherited disease that shares some phenotypic characteristics with AMD, including extensive ECM deposits along Bruch's membrane, RPE, and photoreceptor degeneration, and a high incidence of choroidal neovascularization [Capon et al, 1988[Capon et al, , 1989Hoskin et al, 1981;Sorsby et al, 1949]. Affected persons in two pedigrees with Sorsby's fundus dystrophy have a mutation in the tissue inhibitor of metalloproteinase-3 (TIMP-3) gene [Weber et al, 1994], whose product participates in regulation of ECM turnover [Apte et al, 1995].…”
mentioning
confidence: 99%